Biostimulants in agriculture - Brown, Patrick; Saa, Sebastian (Frontiers in Plant Science, 2015)
Biostimulants, which may be derived from a wide range of natural or synthetic processes, are now widely used in agriculture and yet the mode of action of these materials is not well understood. On the basis of available literature, and based upon the diversity of biostimulant responses highlighted in this focus issue, we hypothesize that biostimulants function by directly interacting with plant signaling cascades or act through stimulation of endophytic and non-endophytic bacteria, yeast and fungi to produce molecules of benefit to the plant. The benefit of the biostimulant is derived from the reduction in assimilates that are diverted to non-productive stress response metabolism.